ECONOMIC AND MATHEMATICAL MODELING IN THE ANALYSIS AND FORECASTING OF THE AUTOMOTIVE INDUSTRY IN UZBEKISTAN - Yakubova Dildar Muxamedjanovna; Kasimova Nozima Omilovna; Saidova Gulnora Amanovna (Scholar Express Journals, 2022)
The use of economic-mathematical models of multifactor static analysis and forecasting is one of the most reliable tools for researching activities of an enterprise or industry as a whole, the study of the dynamics of the industry in the future.
Keywords: Automotive industry; economic and mathematical modeling; multifactor static analysis; forecasting